Mass-Energy-Momentum: Only there Because of Spacetime? - Lehmkuhl, D (2011)
I describe how relativistic field theory generalizes the paradigm property of material systems, the possession of mass, to the requirement that they have a mass-energy-momentum density tensor Tmn associated with them. I argue that Tmn does not represent an intrinsic property of matter. For it will become evident that the definition of Tmn depends on the metric field gmn in a variety of ways. Accordingly, since gmn represents the geometry of spacetime itself, the properties of mass, stress, energy, and momentum should not be seen as intrinsic properties of matter, but as relational properties that material systems have only in virtue of their relation to spacetime structure. © 2011 The Author.